Trunk and upper limb muscle activation during flat and topspin forehand drives in young tennis players - Rogowski, I.; Rouffet, D.; Lambalot, F.; Brosseau, O.; Hautier, C. (Journal of Applied Biomechanics, 2011)
This study compared EMG activity of young tennis players` muscles during forehand drives in two groups, GD—those able to raise by more than 150% the vertical velocity of racket-face at impact from flat to topspin forehand drives, and GND, those not able to increase their vertical velocity to the same extent. Upper limb joint angles, racket-face velocities, and average EMGrms values, were studied. At similar joint angles, a fall in horizontal velocity and a rise in racket-face vertical velocity from flat to topspin forehand drives were observed. Shoulder muscle activity rose from flat to topspin forehand drives in GND, but not for drives in GD. Forearm muscle activity reduced from flat to topspin forehand drives in GD, but muscle activation was similar in GND. The results show that radial deviation increased racket-face vertical velocity more at impact from the flat to topspin forehand drives than shoulder abduction.